(untitled) (Experimental biology, 2017)
The development of new biological tools in the second half of the 20th century gave immense possibilities for genetic engineering and creating new organisms with desirable characteristics. New horizons emerged for agriculture, medicine and environmental area. More than twenty years have passed since the first genetically engineered organisms have been planted in Canada and the USA in the late 1980s. In this article we have analyzed achievements and consequences of the biotechnological applications in agriculture and environmental area.